1987
DOI: 10.1111/j.1432-1033.1987.tb11010.x
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of major platelet proteins in human blood platelets

Abstract: We studied de novo protein biosynthesis in platelets of normal adult donors and in newly formed platelets isolated from splenectomized patients with idiopathic thrombocytopenic purpura (ITP). After metabolic labelling of platelet proteins, performed with different radiolabelled amino acids or carbohydrates, a tenfold increase in incorporation of radioactivity into trichloroacetic-acid-precipitable material was obtained with ITP platelets compared to control platelets. Electron microscopic studies of ITP platel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
155
1
4

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(163 citation statements)
references
References 41 publications
3
155
1
4
Order By: Relevance
“…Although platelets lack a nucleus, they do contain a rough endoplasmic reticulum and polysomes and are known to engage in protein synthesis. 26 The presence of SULT2B1b protein in platelet preparations was confirmed by Western analysis as well as by measuring catalytic activity and the content of cholesterol sulfate produced. The finding of 566 pmol of cholesterol sulfate per 10 9 untreated platelets is in keeping with a previous report where the content of cholesterol sulfate in human platelets was found to range from 164 to 512 pmol/10 9 platelets.…”
Section: Discussionmentioning
confidence: 99%
“…Although platelets lack a nucleus, they do contain a rough endoplasmic reticulum and polysomes and are known to engage in protein synthesis. 26 The presence of SULT2B1b protein in platelet preparations was confirmed by Western analysis as well as by measuring catalytic activity and the content of cholesterol sulfate produced. The finding of 566 pmol of cholesterol sulfate per 10 9 untreated platelets is in keeping with a previous report where the content of cholesterol sulfate in human platelets was found to range from 164 to 512 pmol/10 9 platelets.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated expression of OATP2B1 mRNA in human platelets and megakaryocytes, using real-time RT-PCR. Protein synthesis by anucleated platelets was reported two decades ago (Kieffer et al, 1987), but only recently was de novo synthesis of several polypeptides by human platelets convincingly demonstrated (Lindemann et al, 2001). Denis et al (2005) found constitutive pre-mRNA in human platelets, and critical factors were able to splice it upon activation, generating mature mRNA and new protein.…”
Section: Discussionmentioning
confidence: 99%
“…Besides uptake from plasma, platelets are capable of synthesizing fibrinogen 49 and other proteins through an intact translation machinery that lacks DNA but consists of mRNA, ribosomes, and amino acids. 50 Interestingly, fibrinogen stored in the platelet ␣-granules completely consists of ␥A/␥A fibrinogen.…”
Section: Influence Of the ␥ Chain On Platelet Aggregationmentioning
confidence: 99%